Role of laminin and cognate receptors in cholangiocarcinoma cell migration - Kittiya Islam (Cell Adhesion & Migration, 2021)
Extensive desmoplasia in cholangiocarcinoma (CCA) is associated with tumor aggressiveness, indicating a need for further understanding of CCA cell–matrix interaction. This study demonstrated laminin as the most potent attractant for CCA cell migration and the vast elevation of its receptor integrin β4 (ITGB4) in CCA cell lines. Besides, their high expressions in CCA tissues were correlated with lymphatic invasion and the presence of ITGB4 was also associated with short survival time. ITGB4 silencing revealed it as the receptor for laminin-induced HuCCA-1 migration, but KKU-213 utilized 37/67-kDa laminin receptor (LAMR) instead. These findings highlight the role of ITGB4 and LAMR in transducing laminin induction of CCA cell migration and the potential of ITGB4 as diagnostic and prognostic biomarkers for CCA.